Usefulness of the periodicals of the U.P.- College of Allied Medical Professions (CAMP) Library - Cabral, Dhomilyn C. (2008)
This study evaluated the usefulness of the periodical collection of the CAMP library. It determined whether the educational needs of the CAMP faculty and students are being met with regards to the periodical collection. The main areas focused on are recency, adequacy and comprehensiveness of the collection. The results of the study may serve as guidelines in the planning and formulation of the Library's collection development program. The researcher used the descriptive-survey method to the faculty and students of the UP-CAMP, which is appropriate for disseminating and explaining information applicable in the study. The survey was conducted on the 2nd semester of 2007-2008. Among one hundred seven one (171) respondents, one-hundred fifty (150) of which are students and twenty one (21) are the faculty of the college. The CAMP library periodical collection is adequate in maintaining a health science library.